A Survey of Phonological Mid Vowel Intuitions in Central Catalan. (March 2019) - Renwick, Margaret E L; Nadeu, Marianna
Catalan, like other Romance languages, has two pairs of phonemic mid vowels (/be/ "well" vs. /bɛ/ "lamb"; /os/ "bear" vs. /ɔs/ "bone"). However, these contrasts do not function like others in the language: they are partially phonologically conditioned, and evidence shows that words may be pronounced with different mid vowels by speakers of the same variety or even by the same speaker. Spanish may influence this instability, as first-language Spanish Catalan-Spanish bilinguals struggle to perceive and produce the contrast. This paper investigates the mid vowel contrasts in an Internet survey of vowel height judgments in 220 words by 146 Central Catalan-speaking individuals who also self-reported their language history. Results confirm that certain phonological contexts condition mid vowel height, typically favoring low mid judgments; where phonological conditioning occurs, speakers judge quality with increased consistency and confidence. Many words lacking phonological conditioning environments, however, are variable across speakers. Bilingualism levels and age have an effect: among Catalan-dominant participants, choice of mid vowel is affected by age, while participants with the highest Catalan dominance have greatest confidence in their intuitions. Variably-judged words are also phonetically variable, indicating a word-specific association between strength of phonological representation and realization.